Patients' attitude towards undergraduate medical students at university charity teaching hospital in Sudan - Alawad, Awad Ali M.; Younis, Faisal H. (International Journal of Medicine, 2014)
Background: The cooperation of patients and their acceptance to involve medical students in their care is vital to clinical education. Objective: To explore the attitudes of patients towards medical students at University charity teaching hospital, and to explore the determinants of those attitudes. Methods: This cross-sectional study was conducted at University charity teaching hospital affiliated to University of Medical Sciences and Technology (UMST). Four hundred and thirty-two patients were interviewed between January and December 2013 using a structured questionnaire. Results: Four hundred and thirty-two patients had responded to all questions they were asked. Of the patients interviewed, 95.2% approved the presence of medical students during the medical consultation. 79.8% of the patients agreed to be examined by students in the presence of a doctor, while 33.5% gave agreement even in the absence of a doctor. More than half of the patients think that it is important that students examine patients as part of their training and 18 % of them were not sure about the importance of clinical examination. Conclusion: The study concluded overall positive attitudes to the medical students’ involvement by patients. Patients preferred lower number of students to be involved; however, few were aware of their rights.   Keywords: Bedside Teaching, Clinical Education, Patients’ Acceptability.